Geographical distribution of caudatoside and ptaquiloside in bracken ferns in Northern Europe - Vaidotas Kisielius; Bo Markussen; Hans Christian Bruun Hansen; Lars Holm Rasmussen (Environmental Sciences Europe)
Abstract Bracken ferns (genus Pteridium) are among the most prevalent plants worldwide, with their distribution expanding due to their invasive nature. The environmental implications of their proliferation in areas affected by human activity, natural disasters, or land-use changes are concerning, primarily because of the carcinogenic illudane glycosides they produce. These compounds cause domestic and wildlife animal poisoning, as well as contamination of dairy products and drinking water. Several illudane glycosides are known, but usually only ptaquiloside (PTA) is monitored. This study investigates the spatial and temporal variations in illudane glycosides PTA, caudatoside (CAU) and ptesculentoside (PTE) across two phenotypes of Pteridium aquilinum (vars. aquilinum and latiusculum) over a broad geographic range spanning Denmark, Sweden, and Finland, encompassing 66 locations. We analysed different parts of the fern fronds (the tips and the lowest pinnae) using LC–MS and statistically explored the influence of phenotype, frond part, geographic location, sunlight exposure, and the surrounding ecosystem on glycoside content. Our findings reveal that PTA accounts for approximately two-thirds of the total illudane glycoside content, followed by CAU at nearly one-third, and a minor contribution from PTE. Glycoside levels were not influenced by phenotypic varieties or the studied environmental factors, but were significantly affected by geographic location. Specifically, CAU levels increased progressively towards the northeast, while PTA concentrations were highest in Denmark and markedly decreased in northeastern countries by over threefold, presumably due to climatic gradient. It has been further supported by temporal analysis in selected PTA-dominant regions indicating a reduction in PTA towards the end of the growing season, aligning its levels with those of CAU. Our study highlights that CAU concentrations in bracken ferns may equal or surpass PTA, contesting the prevailing view that PTA is the only notable illudane glycoside in Bracken. To provide unbiased assessment of the potential risks posed by P. aquilinum in the region, environmental and toxicological research should include measurements of not only PTA, but also CAU and, if possible, PTE.